Monitoring Histone Deacetylase Inhibition In Vivo: Noninvasive Magnetic Resonance Spectroscopy Method - Madhuri Sankaranarayanapillai; William P. Tong; Qing Yuan; James A. Bankson; Hagit Dafni; William G. Bornmann; Suren Soghomonyan; Ashutosh Pal; Marc S. Ramirez; Douglas Webb; Kumaralal Kaluarachchi; Juri G. Gelovani; et al. (Molecular Imaging)
Histone deacetylase inhibitors (HDACis) are emerging as promising and selective antitumor agents. However, HDACis can lead to tumor stasis rather than shrinkage, in which case, traditional imaging methods are not adequate to monitor response. Consequently, novel approaches are needed. We have shown in cells that 19 F magnetic resonance spectroscopy (MRS)-detectable levels of the HDAC substrate Boc-Lys-TFA-OH (BLT) are inversely correlated with HDAC activity. We extended our investigations to a tumor xenograft model. Following intraperitoneal injection of BLT, its accumulation within the tumor was monitored by in vivo 19 F MRS. In animals treated with the HDACi suberoylanilide hydroxamic acid (SAHA), tumoral BLT levels were higher by 77% and 132% on days 2 and 7 of treatment compared with pretreatment levels ( n = 6; p < .05). In contrast, tumoral BLT levels remained unchanged in control animals and in normal tissue. Thus, 19 F MRS of BLT detected the effect of HDACi treatment as early as day 2 of treatment. Importantly, tumor size confirmed that SAHA treatment leads to inhibition of tumor growth. However, difference in tumor size reached significance only on day 6 of treatment. Thus, this work identifies BLT as a potential molecular imaging agent for the early noninvasive MRS detection of HDAC inhibition in vivo.